2010
DOI: 10.1371/journal.pone.0015290
|View full text |Cite
|
Sign up to set email alerts
|

Order through Disorder: Hyper-Mobile C-Terminal Residues Stabilize the Folded State of a Helical Peptide. A Molecular Dynamics Study

Abstract: Conventional wisdom has it that the presence of disordered regions in the three-dimensional structures of polypeptides not only does not contribute significantly to the thermodynamic stability of their folded state, but, on the contrary, that the presence of disorder leads to a decrease of the corresponding proteins' stability. We have performed extensive 3.4 µs long folding simulations (in explicit solvent and with full electrostatics) of an undecamer peptide of experimentally known helical structure, both wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The second aspect is the comparison with the experimental data. CHARMM with the CMAP correction, and in agreement with previous studies (2,4,6,15), shows a very strong a-helical bias, to the point of becoming inconsistent with the experimentally determined peptide stability. On the other hand, it correctly predicts the order-disorder pattern of the peptide's N-and C-terminal parts, and by converging to a helical structure, its major cluster is structurally not very different from the deposited NMR models.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The second aspect is the comparison with the experimental data. CHARMM with the CMAP correction, and in agreement with previous studies (2,4,6,15), shows a very strong a-helical bias, to the point of becoming inconsistent with the experimentally determined peptide stability. On the other hand, it correctly predicts the order-disorder pattern of the peptide's N-and C-terminal parts, and by converging to a helical structure, its major cluster is structurally not very different from the deposited NMR models.…”
Section: Discussionsupporting
confidence: 89%
“…From the two sequence variants available for this peptide, we have chosen to simulate the one studied by Araki and Tamura (9) due to the availability of additional (to NMR) experimental data in the form of circular dichroism spectroscopy and self-association studies that verified the peptide's monomeric state in solution. The system preparation procedure and simulation protocol are identical with those we have previously reported (15). In summary, the starting structure (corresponding to the sequence INYWLAHAKAG) was in the fully extended state as obtained from the program Ribosome (http://www.roselab.jhu.edu/~raj/Manuals/ribosome.html).…”
Section: Force Fields System Preparation and Simulation Protocolmentioning
confidence: 99%
“…dynamics of a wide variety of peptide systems. Our perspective on the current literature is that among all extensively tested and validated force fields [25], the AMBER99SB family of force fields and particularly the 99SB � -ILDN and-to a lesser extent-the 99SB-ILDN variants [26][27][28][29] show an outstanding performance against a wide range of systems, from very stable folders [26][27][28][29][30][31] to marginally stable peptides [30][31][32][33][34][35][36][37], and for every structural motif, from mainly helical [27][28][29][31][32][33] to almost exclusively β-hairpin-like [29,31,[37][38][39]. In this communication, we attempt to examine the accuracy of MD simulations and their ability to reproduce the results derived from the aforementioned DFT calculations (of ref 24), as well as experimental data (i.e., Thornton's criteria) [1].…”
Section: Plos Onementioning
confidence: 99%
“…In order to study the propensities of the Asn-Gly segment to form β-turn structures we conducted three MD simulations for the same three capped heptapeptides that Kang and Yoo used in their work: Ac-Ala-Ala-Asn-Gly-Ala-Ala-NHMe (hp NG -1), Ac-Leu-Val-Asn-Gly-Gln-Tyr-NHMe (hp NG -2, from PDB entry 1EST) [44] and Ac-Phe-Val-Asn-Gly-Leu-Phe-NHMe (hp NG -3, derived from an octapeptide with the similar sequence Boc-Leu-Phe-Val-Aib-D-Ala-Leu-Phe-Val-OMe that forms a type I' Aib-D-Ala β-turn) [45]. The system preparation procedure and simulation protocol have been previously described [30][31][32][33][34][35][36][37][38] and in summary were performed as follows. Starting from the fully extended states, addition of missing hydrogen atoms and solvation-ionization were performed with the LEAP program from the AMBER tools distribution.…”
Section: System Preparation and Simulation Protocolsmentioning
confidence: 99%
“…To our knowledge, there is not a single example of a stably folded peptide for which the combination of the AMBER99SB‐ILDN (or AMBER99SB‐STAR‐ILDN) force field with TIP3P water model and full electrostatics has failed to correctly identify the peptide's native state. To the contrary, the aforementioned combination has been shown to be able to accurately predict the structure and dynamics of peptides ranging from very stable folders, to marginally stable peptides, and for all structural motifs from mainly helical to almost exclusively β‐hairpin like . It should be noted, however, that recent studies have indicated the presence of a tendency of these force fields to produce overly compact structures in the case of disordered peptide systems which are known to be rather difficult systems to study with empirical force fields .…”
Section: Introductionmentioning
confidence: 99%